2012
DOI: 10.1007/s13204-012-0124-6
|View full text |Cite
|
Sign up to set email alerts
|

First principles calculation on the structure and electronic properties of BNNTs functionalized with isoniazid drug molecule

Abstract: One-dimensional nanostructures such as nanowires and nanotubes are stimulating tremendous research interest due to their structural, electronic and magnetic properties. We perform first principles calculation using density functional theory on the structural, and electronics properties of BNNTs adsorbed with isoniazid (INH) drug via noncovalent functionalization using the GGA/PBE functional and DZP basis set implemented in SIESTA program. The band structure, density of states and projected density of states (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…5-FU has emerged excellent anticancer activity in human breast cancer cells (MCF-7) using multi-walled carbon nanotube adapted graphite electrode that applies cyclic voltammetry (CV) and potentiometric stripping analysis [14][15][16]. Recently, Deka and co-worker reported the interaction of (10, 0) and (5,5) BN nanotubes functionalized with isoniazid (INH) drug molecule, they have shown that the binding energy of INH upon (5,5) BNNT is slightly considerable than that of (10, 0) BNNT [17]. Pandey et al demonstrated the adsorption of tryptophane (nonpolar amino acid), asparatic acid and argenine (polar amino acids) upon the surface of BN nanotubes, indicating for a strong binding energy with polar amino acids, asparatic acid and argenine, on the tube surface [1].…”
Section: Introductionmentioning
confidence: 99%
“…5-FU has emerged excellent anticancer activity in human breast cancer cells (MCF-7) using multi-walled carbon nanotube adapted graphite electrode that applies cyclic voltammetry (CV) and potentiometric stripping analysis [14][15][16]. Recently, Deka and co-worker reported the interaction of (10, 0) and (5,5) BN nanotubes functionalized with isoniazid (INH) drug molecule, they have shown that the binding energy of INH upon (5,5) BNNT is slightly considerable than that of (10, 0) BNNT [17]. Pandey et al demonstrated the adsorption of tryptophane (nonpolar amino acid), asparatic acid and argenine (polar amino acids) upon the surface of BN nanotubes, indicating for a strong binding energy with polar amino acids, asparatic acid and argenine, on the tube surface [1].…”
Section: Introductionmentioning
confidence: 99%
“…Occurring substantial changes in BNNT systems' electronic properties is carried out after these hetero-cycles' attachment to the tube surface; however, DOS plots, natural bond orbital (NBO) analysis and the quantum molecular descriptors (QMD) are evidences of these changes. Moreover, different molecules, and [p-(1,1,3,3-tetramethylbutyl)phenyl ether (Triton X-100) [80], isoniazid [81], amine [82], methanol [83] are also explored for functionalization of BNNTs.…”
Section: Theoretical Investigationsmentioning
confidence: 99%
“…Its electrochemical behavior has prominent impacts on its physiological functions which is an essential factor in the diagnosis of some diseases in clinical medicine [22]. For example, the adsorption of isoniazid drug molecule toward the electronic and structural properties of (5,5) and (10,0) BN nanotubes were studied by Deka et al [23]. They reported that the interaction of drug molecules with (10,0) BNNT is thermodynamically notable in comparison with (5,5) BNNT.…”
Section: Introductionmentioning
confidence: 99%